Квантовохімічне моделювання впливу адсорбції молекул води та метанолу на параметри фазового переходу діоксиду ванадію - Kaurkovskaya, V. N.; Grebenyuk, A. G.; Lobanov, V. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2015)
A theoretical; study on the effect of interaction between vanadia surface and wateror methanol molecules on the temperature of phase transition (PTT) has been carried out within the frameworks of Hartree-Fock-Roothaan method with use of minimal cluster model. The phase before transition was singlet whereas those after transition were respective high spin state. The PTT values for such models have been shown to differ from those for bulk; nevertheless their changes due to adsorption reflect the experimental tendencies.